2014
DOI: 10.1002/cjg2.20113
|View full text |Cite
|
Sign up to set email alerts
|

In‐Situ Stress Measurements and Slip Stability of Major Faults in Beijing Region, China

Abstract: In order to estimate the upper crustal stress state and slip stability of major faults after the Wenchuan Ms 8.0 earthquake, five boreholes, i.e., Pinggu, Shisanling, Xifengsi, Miyun, and Lisiguang Memorial Hall borehole ranging from 600 to 1000 m were drilled in Beijing region. Hydraulic fracturing method was used to conduct in-situ stress measurements in these five boreholes, and stress monitoring equipment was installed at appropriate depth and monitoring stations were constructed. Those data derived from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Wild-type strains Dazao ( + p ) and melanic mutant strains p M , p S and p B (Xiang 1995; Banno et al 2005; Yoda et al 2014) were analyzed in this study. The darkness of pigment was measured as mean OD value using Image J (https://imagej.nih.gov/ij/).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Wild-type strains Dazao ( + p ) and melanic mutant strains p M , p S and p B (Xiang 1995; Banno et al 2005; Yoda et al 2014) were analyzed in this study. The darkness of pigment was measured as mean OD value using Image J (https://imagej.nih.gov/ij/).…”
Section: Methodsmentioning
confidence: 99%
“…In the Lepidoptera model, Bombyx mori , an intriguing phenomenon has been reported that a larval melanic mutant, Striped ( p S , 2-0.0) is able to rehabilitate the malformed body shape, as well as the adaptability defects of the stony mutant ( st , 8-0.0) (Xiang 1995; Banno et al . 2005).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations